New approaches to Latin American studies
1 online resource
Keywords: Academic and research fields are moved by fads, waves, revolutionaries, paradigm shifts, and turns. They all imply a certain degree of change that alters the conditions of a stable system, producing an imbalance that needs to be addressed by the field itself. New Approaches to Latin American Studies: Culture and Power offers researchers and students from different theoretical fields an essential, turn-organized overview of the radical transformation of epistemological and methodological assumptions in Latin American Studies from the end of the 1980s to the present. Sixteen chapters written by experts in their respective fields help explain the various ways in which to think about these shifts. Questions posited include. Why are turns so crucial. How did they alter the shape or direction of the field. What new questions, objects or problems did they contribute. What were or are their limitations. What did they displace or prevent us from considering. Among the turns included: memory, transnational, popular culture, decolonial, feminism, affect, indigenous studies, transatlantic, ethical, post/hegemony, deconstruction, cultural policy, subalternism, gender and sexuality, performance, and cultural studies.